Comparison of IgG-ELISA and IgG4-ELISA for Toxocara serodiagnosis - Noordin, R.; Smith, H.V.; Mohamad, S.; Maizels, R.M.; Fong, M.Y. (Elsevier, 2005)
Diagnosis of human toxocariasis, caused by Toxocara canis or Toxocara cati, normally relies on a combination of the presence of clinical signs and symptoms backed by positive serology. The use of Toxocara excretory-secretory antigen (TES) in ELISA assays increases the test specificity. However, in tropical countries where soil-transmitted helminths are endemic, cross-reactivity from antibodies to these intestinal parasites poses a significant limitation for Toxocara serodiagnosis. To increase the specificity of serodiagnosis, we compared the use of IgG-ELISA to the use of IgG4-ELISA using commercially manufactured TES-coated plates. The sensitivity of the IgG-ELISA was 97.1, while that of the lgG4-ELISA was 45.7; the specificities were 36.0 and 78.6, respectively. The study shows that employing both assays can improve the serodiagnosis of toxocariasis. An IgG4 immunoassay would also be useful in the secondary screening of antigen clones in the effort to develop improved serological tests for toxocariasis. (C) 2004 Elsevier B.V. All rights reserved.